The effect of psychological distance on online advertising: A case study of video enrollment advertisement of colleges - HE, Xian (Institutional Knowledge at Singapore Management University, 2023)
Advertising for enrolment through the Internet has become an important means of enrolment promotion in Chinese universities. However, there is currently no clear research conclusion on how to conduct effective advertising, especially on the selection of factors such as promotion time, promotion platform, and promotion targets. Based on the construal level theory, this study investigated the effects of different types of college enrolment advertising on different new media platforms, using different dimensions of psychological distance corresponding to factors such as promotional time and promotional area. The empirical results show that different advertising types do have significant effect differences on different groups. “Desirable” information is more effective for parents, while the students pays attention to both “desirable” information and “feasible” information at the same time. There are also differences in the publicity effect of different platforms. In the empirical study, the information published on the Kwai and Douyin is more effective to the students, while the information published on the “Moments” is more effective to the parents.